Kant or Schmitt? Philosophical-political perspectives of thearmed conflict. (2008)
This article analyzes Immanuel Kant’s and Carl Schmitt’s philosophical views in order to find theoretical referents for the understanding and termination of the Colombian armed conflict. For that purpose the work appeals basically to the study of such tex